Navigating Non-Academic Challenges of International Students: A Case Study at an Islamic University in Indonesia - Syahriani, Ririn; Sain, Yulianah (Jurnal Genesis Indonesia, 2025)
The internationalization of higher education creates both benefits and challenges for international students. While academic issues are routinely prioritized, non-academic challenges such as homesickness, culture shock, and social isolation are sometimes disregarded. This study looks at the non-academic experiences of international students at an Islamic University in Indonesia. Using qualitative interviews and thematic analysis, this study identifies substantial problems in students' assimilation to local culture, as well as the effectiveness of institutional support. The findings suggest that colleges should broaden their support services beyond academics to include emotional and social well-being. This study adds to the overall understanding of international student experiences and makes recommendations for non-Western higher education institutions.